INTEGRASI SAINS DAN AGAMA DALAM PERSPEKTIF ETIKA - Kholil, Ahmad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2009)
The dichotomy between religion and non-religion knowledge has existed in the Islamic classical thought. However, dichotomy has not impacted much on the intellectual matters. In the perception of classical ulama both of the knowledge was considered important, therefore, both were necessary to be mastered. The pioneered ulama on the science and deeds recognized the validity and scientific position of each group. It is different from the western modem sciences that often denied and downgraded the religious knowledge. However, the western science perception influenced Moslem society through imperialism. It emerged a strict dichotomy between religion knowledge taught in the (traditional) Islamic education and the (secular) non-religion knowledge taught in general education institutions. The Islamic knowledge perspective has viewed that natural phenomena do not happen without any relation with Ilahi’s power as the phenomena are not more than the God’s creative area. Therefore, learning the non-religious knowledge and understanding closely God’s creation system is significant.